2021
DOI: 10.1029/2020gb006821
|View full text |Cite
|
Sign up to set email alerts
|

Glacial Dust Surpasses Both Volcanic Ash and Desert Dust in Its Iron Fertilization Potential

Abstract: The Arctic and subarctic Pacific Ocean is experiencing rapid change as a result of climate warming and associated feedbacks (Grebmeier et al., 2006;Gregg et al., 2003;Serreze et al., 2007). The northeastern Pacific Ocean and the Bering Sea are characterized as high nutrient, low chlorophyll (HNLC) regions due to limited iron (Fe) inputs. Global satellite-based measurements of primary production suggest a large decrease in the North Pacific region (−9.3%) between the early 1980s and the early 2000s, associated … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
47
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(50 citation statements)
references
References 134 publications
(306 reference statements)
3
47
0
Order By: Relevance
“…Given our currently limited understanding of the factors controlling metal delivery, solubility, and persistence in glacier‐ocean systems (Hopwood et al., 2019), it remains challenging to put these first observations of metal micronutrient concentrations in CAA glacierized regions into a more complete context with other systems. However, data from the Gulf of Alaska offers the prospect that riverine particulate Fe may provide a key supply of offshore bioavailable Fe to surrounding Fe‐limited marine waters (Crusius et al., 2011; Koffman et al., 2021; Schroth et al., 2011). Clearly, there is a need for better spatial and chemical resolution of metal micronutrient dynamics in CAA systems specifically, and in glacier‐influenced systems more generally.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given our currently limited understanding of the factors controlling metal delivery, solubility, and persistence in glacier‐ocean systems (Hopwood et al., 2019), it remains challenging to put these first observations of metal micronutrient concentrations in CAA glacierized regions into a more complete context with other systems. However, data from the Gulf of Alaska offers the prospect that riverine particulate Fe may provide a key supply of offshore bioavailable Fe to surrounding Fe‐limited marine waters (Crusius et al., 2011; Koffman et al., 2021; Schroth et al., 2011). Clearly, there is a need for better spatial and chemical resolution of metal micronutrient dynamics in CAA systems specifically, and in glacier‐influenced systems more generally.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, both glacial sediments and meltwater have been shown to be enriched in iron (Fe) and some other metal micronutrients like manganese (Mn) as a result of weathering processes, suggesting that this meltwater may serve as a direct source of metals to the ocean (Bhatia et al., 2013; Hawkings et al., 2014; Koffman et al., 2021). Previous work in the Gulf of Alaska in particular has highlighted the role that glacial sediments play in providing a source of bioavailable Fe to the surrounding ocean (Crusius et al., 2011; Koffman et al., 2021; Schroth et al., 2011). However, many unknowns remain about how much of the metals delivered by glacier meltwater is ultimately bioavailable in the ocean (Hopwood et al., 2019; Wadham et al., 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The Mississippian (and Upper Devonian) of North America contain anomalously high organic carbon, with the Woodford Shale and correlatives considered world-class source rocks (Ulmishek and Klemme 1990;Kuuskraa 2011;Sonnenberg 2011). We speculate that this remarkable organic richness might reflect eolian delivery of abundant nutrients (notably iron) to these distal epeiric seas, stimulating productivity and associated preservation of organic carbon, as has been observed in the Bering Sea (Koffman et al 2021) and suggested in other deep-time, dust-sourced systems (e.g., Carroll et al 1998;Gabbott et al 2010;Sur et al 2015;Abadi et al 2020).…”
Section: Origin Of Voluminous Mid-paleozoic Siltmentioning
confidence: 59%
“…We followed the thorium-based mass balance approach of Serno et al (2014) to calculate the relative proportions of Asian dust and volcanogenic material in Core LV63-4-2 (Text S4 and Figure S4 in Supporting Information S1). The Hm and Gt content is about one order of magnitude higher in Asian dust than in volcanogenic material (Koffman et al, 2021) (Figure S4b (Cheng et al, 2016) and Northern Hemisphere summer insolation (65°N, July-September) (Laskar et al, 2004); (b) Precession index (Laskar et al, 2004); (c) Reconstructed East Asian monsoon precipitation in its northern region based on records of 10 Be in loess (Beck et al, 2018) and δ 13 C of loess carbonate (Sun et al, 2019); (d) Hm/(Hm + Gt) ratio (original data and three-point filter) in core LV63-4-2, and 21 kyr Gaussian bandpass filtered output (thick red line); (e) Rel Hm + Gt content (original data and threepoint filter) in core LV63-4-2, and 41 kyr Gaussian bandpass filtered output (thick purple line); (f) Rel Hm + Gt flux (mg/cm 2 /kyr, gray line) in core LV63-4-2, 41 kyr (thick gray line) and 21 kyr (thick pink line) Gaussian bandpass filtered output; (g) Dust flux record from core V21-146 on Shatsky Rise (Hovan et al, 1989) (line with symbols), and obliquity index (Laskar et al, 2004) (Lisiecki & Raymo, 2005) and atmospheric CO 2 concentrations from EPICA Dome C ice core (Lüthi et al, 2008). Gray bars indicate glacial periods, and all periods are labeled with marine isotope stage (MIS) numbers.…”
Section: Hematite and Goethite As Proxies For Eolian Input In North P...mentioning
confidence: 92%